Pengaruh Kualitas Pelayanan, Harga dan Kepercayaan Konsumen terhadap Keputusan Penggunaan Jasa Pencucian Mobil Si Galuh Samarinda - Masrulin Dwi Manfi (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The purpose of this study was to determine the effect of Service Quality, Price and Consumer Trust on Service Usage Decisions at Si Galuh Car Wash. There are three independent variables in this study, namely Service Quality (X1), Price (X2) Consumer Confidence (X3) and one dependent variable, namely Service Use Decision (Y). The number of samples in this study were 100 consumers in Si Galuh Car Wash and data analysis used SPSS version25 software. The tests carried out in this study are validity test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient test, determination coefficient test, t test and f test. The results in this study are the service quality variable partially has a positive and significant effect while the price and consumer trust variables partially have a positive but insignificant effect on the decision to use services at Si Galuh Car Wash. The results of the f test (simultaneous) show that service quality, price and consumer trust simultaneously have a positive and significant effect on the decision to use services at Si Galuh Car Wash. There are deficiencies in Si Galuh Car Wash, namely the less comfortable waiting room, this is evidenced by 44 of the 100 respondents who were researched, 44 stated that the waiting room at Si Galuh Car Wash was uncomfortable and 16 people stated that it was uncomfortable. It is recommended that Si Galuh Car Wash create a more comfortable waiting room for consumers so that consumers who wash their vehicles can feel comfortable while waiting for their vehicles to be washed.